The Presence of Artemis Related to her Cult in Three Hellenistic Novels: Chaereas and Callirhoe, Ephesiaca, and Leukippe and Kleitophon, Based on the Greek Landscape - Salas-Moya, Jenny (2025)
The article proposed to analyze the presence of Ártemis in three Hellenistic novels: The objective is to determine the link between the cultic practice related to the goddess and the Greek landscape of Antiquity. This will be achieved by examining the works Chaereas and Callirroe, Anthia and Habrocomes and Leucipa and Clitophon. Based on the mention of elements of the Greek religious landscape of Antiquity, such as the mountains (ourea), the temple, the sanctuary, the location of these and the natural environments associated with Artemis, as well as on the mention of the aspects of the cult present in processions or sacrifices, the hunting function of the goddess in the texts was highlighted. Likewise, with the purpose of enriching the proposed analysis, we resorted to the references on the subject present in the Epic, some mentions in the Lyric, and in the Drama, specifically in the Tragedy, genres that permeated the Hellenistic novel, and that in the particular case of this research were fundamental.